EFEKTIVITAS PEMBELAJARAN LARI CEPAT MELALUIÂ METODE PERMAINAN BOKAKUN (STUDI PADA SISWA KELAS V SDN BALASKLUMPRIK I/434 SURABAYA) - PRASTYA SETIAWAN, BAGUS (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sometimes we ignore the effectiveness in depth, although it’s needed for learning process. Because it can be as measure of success in learning activities.The learning effectiveness will happen if we’re using teaching method, that’s the way of teaching. To make it happens, teacher has to use bokakun as the game method, that is a basic of sprint game with Ball, funnel and box as the tools. It’s so easy to do and it’s very useful to stimulate students in sprint learning process. Sprint is the one of sports and it’s very easy to do.Research methods for this activity were pre test and post test, I was using One Group Pretest - Posttest Design as the design also the instruments, they were : (1). Observation Sheet of Dikjasor Class, this observation used as pre test and post test consideration in the learning process, (2). FCE Paper (Formative Class Evaluation) was being used for knowing student’s opinion in the learning process that we’d done, (3). Column of Study Evaluation  was used for knowing the study result, especially in the learning  process.Based from SPSS data result, from 33 students that had the test, it was α (0.05), Z value was  -2,530b  and sig value was 0.11. It showed that there was a distinction, if Sig < α (0.05) so HA had been accepted. It means that there was an effect if we’re using BOKAKUN in sprint learning process especially in depth of effectiveness and got 3,38 % for grew of study result. Finally, we could take a conclusion from this research activity that if there is Sig < α (0.05) so the HA will be accepted and it will be showing to us a differencies between them. The conclusion from the effectiveness fifth grade of sprint for student in SDN Balaskrumpik I/434 Surabaya with Bokakun game method is this game has good effect and effective for sprint  learning activity and increasing the study result of student in sprint subject. Keywords: The effectiviness of studying sprint, game of bokakun